Dry material formula optimization design method for graphite electrode contact

By crushing and sieving large pieces of materials in the dry material formula of graphite electrode joints, the optimal ratio of large particles and powder was calculated, which solved the production problems caused by human error, improved product density and physical and chemical indicators, and reduced the Production cost.

CN119118104APending Publication Date: 2024-12-13JILIN CARBON
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411299255.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In the existing dry material design of graphite electrode joints, artificial errors lead to reduced calcination density, increased graphitization difficulty, extended calcination time and unfavorable product physical and chemical indicators, resulting in production costs and product quality problems.

Method used

By crushing and screening large pieces of 2-1mm and 1-0.5mm particle size, the optimal ratio of large particles and powder is calculated to reduce the asphalt demand by measuring the effective density and mixing ratio of different particle sizes. , increase density.

Benefits of technology

It reduces production costs, improves product density and physical and chemical indicators, reduces the use of asphalt, and improves the accuracy of formula calculation and product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a dry material formula optimization design method for a graphite electrode contact, and belongs to the technical field of graphite electrode formulae, the dry material formula design method comprises the following steps: crushing a large block material in unit volume, and directly adopting the output ratio of particles with the particle sizes of 2-1mm and 1-0.5 mm after the crushed large block material in unit volume is screened as the use ratio of the formula; the use ratio of particle raw materials with the particle sizes of 2-1mm and 1-0.5 mm does not need to be calculated in advance, the effective density of particles with the particle sizes is measured, the matching ratio of a mixture of the particle raw materials with the small particle sizes matched with the particles with the particle sizes and powder is calculated, meanwhile, the optimal purity of the powder is obtained through experiments, and the optimal dry material formula of the graphite electrode connector is calculated, so that the product quality is improved. The density of the roasted product is higher, meanwhile, the demand quantity of the asphalt is controlled, and gaps of large particles need to be filled with the minimum powder, so that the quality of the produced graphite electrode product is improved, and meanwhile, the production cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention patent relates to the technical field of graphite electrode formulation, in particular to a method for optimizing the design of dry material formulation for graphite electrode joints. Background Art

[0002] Graphite electrode joints are accessories of graphite electrodes and are used in conjunction with graphite electrodes. Graphite electrodes will gradually consume during use and become shorter and shorter. In large-scale industrial production, two or more electrodes need to be connected end to end before use to reduce the frequency of shutdowns and replacements. Therefore, the production of graphite electrode joints and the composition of their dry material particle size are particularly important. Existing design methods include the triangle maximum density selection method, the mixture maximum tap density optimization method, the appropriate density method, and the orthogonal experimental method.

[0003] Chinese invention patent CN113860874A-A design method for dry material particle size composition in graphite electrode joint formula, gives a design ratio method for dry material in graphite electrode joint formula, the particle size group is divided into large particle group and powder group, wherein the large particle group includes two particle sizes A and B, the powder group includes particle size C, a part of the A particle size material is replaced by another material B particle size, the replacement ratio is gradually increased until it is completely replaced, and the stacking density test is performed on the mixed materials of A and B in different proportions. The largest stacking density is the best ratio. The product is produced after pressing and roasting. The roasting volume density is measured. The formula with the highest volume density after roasting is determined as the best use ratio of large particle group and powder. The maximum particle size and the use ratio of powder are confirmed to form a complete dry material particle size composition formula.

[0004] In the above method, the method of confirming the ratio of 2-1mm and 1-0.5mm particle sizes and powder materials according to the existing mixed stacking density is relatively complicated, and dozens of mixed stacking experiments are required to find the best ratio. However, human errors will occur repeatedly in manual operations. The superposition of multiple human errors makes the final actual production results deviate greatly from the theoretical results, resulting in large errors in actual production. At the same time, it causes larger gaps after the mixed dry materials are stacked, and the required binder asphalt increases. The increase in the use of asphalt has the following disadvantages:

[0005] 1. The roasting density is reduced. Asphalt volatilizes and cokes during roasting, and the coking value is between 50% and 60%, that is, the volatilization loss weight is between 40% and 50%. Therefore, the more asphalt in the product, the greater the heat loss weight of the roasted product, and the lower the density of the roasted product;

[0006] 2. The difficulty of graphitization increases. Pitch coke is a coke that is difficult to graphitize. The increase in the amount of asphalt means the increase in the amount of asphalt coke. In order to achieve the same degree of graphitization, the amount of electricity delivered in the graphitization process must be increased, which leads to higher costs.

[0007] 3. Roasting time increases, gas consumption increases. Since the roasting process is the coking process of asphalt at high temperature, a large amount of volatiles will be removed during the coking process. The removal of volatiles will have an impact on the product, causing cracks in the product. In order to protect the product from being cracked by the impact of volatiles, the heating rate must be reduced and the roasting time must be extended, thereby reducing the removal rate of volatiles per unit time. This leads to an increase in roasting gas consumption, increasing the roasting time cost and gas cost;

[0008] 4. The physical and chemical indicators of the product are unfavorable. The pitch coke obtained by roasting cannot form a longitudinal orientation arrangement during extrusion molding like needle coke. Therefore, the pitch coke in the product does not have anisotropy. This is inconsistent with the longitudinal direction of the current when the product is used, resulting in increased self-heating of the product and accelerated burning.

[0009] Therefore, in order to solve the above problems, it is urgent to invent a dry material formula optimization design method for graphite electrode joints to solve the above problems. Summary of the invention

[0010] The present invention discloses a method for optimizing the dry material formula design of a graphite electrode joint. Compared with the traditional process, the traditional process uses a calculated block particle size for mixing. The present dry material formula design method uses a planned large block material and crushes the large block material. The present design does not need to calculate the usage ratio of large particles. The ground and crushed powder is mixed with asphalt to bond the crushed large particles and small particles, so that the gap between the large coke pieces is minimized and the filling powder demand is minimized, thereby achieving the minimum asphalt demand, the highest density, and reducing production costs.

[0011] The present invention discloses a method for optimizing the dry material formula of a graphite electrode joint, comprising the following steps:

[0012] (1) Limiting the particle size of 2-1mm and 1-0.5mm: Take a unit volume of large blocks and crush them to a particle size of less than 2mm, and screen the resulting crushed materials according to different particle sizes;

[0013] (2) The yield ratio of particles with a particle size of 2-1 mm and 1-0.5 mm in the sieved crushed material is determined as B:1: The effective density of particles with a particle size of 2-1 mm is determined as d 2-1 , the effective density of the particle size of 1-0.5 mm is determined as d 1-0.5 ;

[0014] (3) Determine the mixing ratio of the 0.5-0 mm particle size undersize material and the powder of fixed purity;

[0015] (4) Conducting a tap density test on 50 g of mixed large particles, and calculating the proportions of particles with a particle size of 2-1 mm, particles with a particle size of 1-0.5 mm, particles with a particle size of 0.5-0 mm, and powders with a fixed purity in the technical formula;

[0016] (5) Calculate the wet mixing time in the kneading time.

[0017] Preferably, the step (2) is specifically:

[0018] The effective volume and mass of the 2-1mm and 1-0.5mm sized particles after screening were measured, and the d was determined by the ratio of the mass to the effective volume. 2-1 and d 1-0.5 .

[0019] Preferably, the step (3) is specifically:

[0020] The 0.5-0 mm small particles after screening were further screened to obtain 0.075-

[0021] The content of 0mm in 0.5-0mm particle size is K%, and 0.5-0mm particle size and fixed purity powder are mixed. When the proportion of 0.5-0mm in the mixture is X, the proportion of powder in the mixture is Y, and the purity of the fixed purity powder is N%, the effective density of the mixture is measured as d 粉料 , the proportion of 0.075-0mm in the mixed material is:

[0022] After the needle coke material is mixed, the content of 0.075-0 mm accounts for 56%;

[0023] After the roasted and crushed materials are mixed, the content of 0.075-0 mm accounts for 54% of the materials;

[0024] After petroleum coke materials are mixed, the content of 0.075-0mm accounts for 55%;

[0025] Taking needle coke as an example, the calculation is as follows:

[0026] X+Y=100% Formula 1

[0027] X×K%+Y×N%,=56%; Formula 2

[0028] The mixing ratio of small particles with a particle size of 0.5-0 mm after screening and powder with a fixed purity is A:1

[0029] Preferably, the particle size of 0.075-0 mm is further divided into 0.015-0 mm, 0.038-0.015 mm and 0.075-0.038 mm, and the filling amount of each particle size is controlled so that the particle sizes within 0.075-0 mm are filled with each other.

[0030] Preferably, the fixed purity powder has a purity of 80%.

[0031] Preferably, the step (4) is specifically:

[0032] Take 50 grams of mixed large particles of 2-1mm and 1-0.5mm with a mixing ratio of B:1 for tap density test, and measure its volume as V. Calculate the effective volume V1 of 50g mixed particles, which is calculated as follows:

[0033] V1=[(50×B) / (B+1)] / d 2-1 +[(50×1) / (B+1)] / d 1-0.5 Formula 3

[0034] The void volume in 50g of mixed particles is V2, V2 = V-V1

[0035] The mass D of the mixed powder that can be filled in V2 is calculated as follows:

[0036] D=V2×d 粉料 Formula 4

[0037] The percentage of mixed powder to the sum of 50 grams of mixed particles and mixed powder is E 粉料 , calculated as follows:

[0038] E 粉料 =[D / (D+50)]×100% Formula 5

[0039] The percentage of 2-1mm particle size particles in the technical formula is C 2-1 , the percentage of 1-0.5mm particle size in the technical formula is C 1-0.5 , calculated as follows:

[0040] C 2-1 =(100%-E 粉料 )×[B / (B+1)]

[0041] Formula 6

[0042] C 1-0.5 =(100%-E 粉料 )×[1 / (B+1)] Formula 7

[0043] The percentages of 0.5-0 mm particle size particles and powders of fixed purity in the technical formula are C 0.5-0 , C 粉料 , calculated as follows:

[0044] C 0.5-0 =E×A / (A+1) Formula 8

[0045] C 粉料 =E×1 / (A+1) Formula 9

[0046] Preferably, the step (5) is specifically:

[0047] The wet mixing time in the kneading time is calculated as follows:

[0048] [(C 2-1 +C 1-0.5 -27%)×2.5 / 10%]+40 Formula 10 Preferably, 27% in the wet mixing time is the percentage of 2-1mm and 1-0.5mm in the initial technical formula, and 40 in the wet mixing time is 40min in the original technical formula.

[0049] Beneficial Effects

[0050] The present invention changes the calculation method of the dry material formula of the graphite electrode joint, and adopts the method of crushing the large material blocks of the required unit amount, without the need to calculate the proportion of the large particles after crushing. By screening the different particle sizes after crushing, the volume and mass of the large particles are measured, and the effective density of the large particles is calculated, so as to deduce the percentage of small particles that need to be used and the percentage of powder with fixed purity, so as to obtain the optimal formula ratio corresponding to the large particles after crushing. Compared with the prior art that requires more data to be manually measured, this operation method effectively reduces human errors and improves the calculation accuracy of the dry material formula.

[0051] The present invention uses the concept of effective density of materials to calculate the ratio of mixed large particles to powder, and calculates the minimum amount of powder required to completely fill the gaps in the large particles. Such an amount of powder brings the least amount of use while meeting the filling effect and the least asphalt demand, thereby making the overall formula more reasonable, increasing the product volume density, reducing the amount of asphalt used, improving product quality, and reducing the company's production costs. DETAILED DESCRIPTION

[0052] The present invention discloses a method for optimizing the dry material formula of a graphite electrode joint, comprising the following steps:

[0053] (1) Limiting large particles: Take a unit volume of large blocks and crush them to a particle size of less than 2 mm. The resulting crushed materials are sieved according to different particle sizes. The sieved particle sizes are: 2-1 mm, 1-0.5 mm, and 0.5-0 mm.

[0054] (2) The yield ratio of large particles with a particle size of 2-1 mm and 1-0.5 mm in the sieved crushed material is determined to be B:1, and the effective density of particles with a particle size of 2-1 mm is determined to be d 2-1, the effective density of the particle size of 1-0.5 mm is determined as d 1-0.5 , the ratio of the measured mass to the effective volume of the particle size is the effective density.

[0055] (3) The 0.5-0 mm small particles after crushing are further screened, and the content of 0.075-0 mm in the 0.5-0 mm particle size is K%. The powder with a particle size of 0.5-0 mm and a fixed purity is mixed. When the proportion of 0.5-0 mm in the mixture is X, and the proportion of powder in the mixture is Y, the effective density of the mixture is measured as d 粉料 , the proportion of 0.075-0mm in the mixed material meets the following proportions:

[0056] After the needle coke material is mixed, the content of 0.075-0 mm accounts for 56%;

[0057] After the roasted and crushed materials are mixed, the content of 0.075-0 mm accounts for 54% of the materials;

[0058] After petroleum coke materials are mixed, the content of 0.075-0mm accounts for 55%;

[0059] Taking needle coke as an example, the calculation is:

[0060] X+Y=100%

[0061] X×K%+Y×80%=56%;

[0062] The mixing ratio of 0.5-0mm undersize material and fixed purity powder is A:1

[0063] A=X / Y

[0064] (4) Take 50 grams of mixed large particles of 2-1 mm and 1-0.5 mm with a mixing ratio of B:1 for tap density test, and measure its volume as V. Calculate the effective volume V1 of 50g mixed particles:

[0065] V1=[(50×B) / (B+1)] / d 2-1 +[(50×1) / (B+1)] / d 1-0.5 ;

[0066] Calculate the void volume V2 in 50 g of mixed particles:

[0067] V2 = V - V1;

[0068] The mass D of the mixed powder that can be filled in V2 is:

[0069] D=V2×d 粉料 ;

[0070] Calculate the percentage of mixed powder in the sum of 50 grams of mixed particles and mixed powder E 粉料 :

[0071] E 粉料 =[D / (D+50)]×100%;

[0072] Calculate the percentage of 2-1 mm particle size in the technical formula as C 2-1 , calculate the percentage of 1-0.5mm particle size in the technical formula as C 1-0.5 ,

[0073] C 2-1 =(100%-E 粉料 )×[B / (B+1)];

[0074] C 1-0.5 =(100%-E 粉料 )×[1 / (B+1)];

[0075] Calculate the percentage of 0.5-0 mm sieve material and fixed purity powder in the technical formula as C 0.5-0 , C 粉料

[0076] C 0.5-0 =E×A / (A+1);

[0077] C 粉料 =E×1 / (A+1);

[0078] (5) The duration of wet mixing time in the kneading time is (in minutes):

[0079] [(C 2-1 +C 1-0.5 -27%)×2.5 / 10%]+40.

[0080] In some embodiments, the 0.075-0 mm particle size is further divided into 0.015-0 mm, 0.038-0.015 mm and 0.075-0.038 mm, and the filling amount of each particle size is controlled so that the particle sizes within 0.075-0 mm fill each other, and the mixed material is filled more fully.

[0081] In some embodiments, when the fixed purity powder is 80%, the density of the raw product after molding and the density of the baked product after calcination are both greater and the amount of oil used is relatively lower, so that some products can reduce one impregnation and one calcination process and the physical and chemical indicators are more in line with the needs of product users.

[0082] In some embodiments, 27% of the wet mixing time is the percentage of 2-1 mm and 1-0.5 mm in the initial technical formula, and 40 is the wet mixing time (in minutes) in the initial technical formula. The initial technical formula is shown in Table 1 below:

[0083] Table 1: Original technical formula of dry materials for graphite electrode joint raw products

[0084] Particle size (mm) 2-1 1-0.5 0.5-0.15 0.15-0 0.075-0 Particle size ratio (%) 15 12 15 58 45

[0085] Example 1

[0086] In a specific embodiment provided by the present invention, the optimal mixed powder ratio calculation process and formula: the 0.075-0mm content in the 0.5-0mm particles of the 0.5mm sieve is measured as E%, and the 0.5-0mm particle size and 80% powder are mixed to produce the optimal powder purity of needle coke 56% calculation steps are as follows:

[0087] Assuming the total amount of the mixture is 1, when the proportion of 0.5-0mm in the mixture is X, the proportion of 80% powder is Y.

[0088] Then X+Y=100%; X×E%+Y×80%=56%;

[0089] Where E% is the known result after measurement, so there are only unknowns X and Y in the above formula, when: X:Y=A:1;

[0090] Similarly, the formula for determining the optimal powder purity mixing ratio of other raw materials is the same, and the optimal powder purity value of the raw materials is obtained as follows:

[0091] Needle coke: 56%; calcined coke: 54%; petroleum coke: 55%.

[0092] Example 2

[0093] In a specific embodiment provided by the present invention, mixed powders with different powder purities are used for comparison:

[0094] The five powder purities of 70%, 75%, 80%, 82%, and 84% and the mixed powder with a particle size of 0.5-0 mm and a powder purity of 56% were compared in the test. The comparative data are shown in Table 2 below:

[0095] Table 2: Comparison of the purity of Φ333mm graphite electrode common joint powder and the mixed powder with a particle size of 0.5-0mm and a purity of 56%

[0096]

[0097] From the data in the above table, we can see that the density of No. 3 and No. 5 after roasting is large and similar. No. 3 sample uses relatively less oil and has lower heat loss during roasting. No. 3 sample is the optimal solution, that is, the powder with 80% purity and 0.5-0mm mixed sample powder is suitable for product use.

[0098] Example 3

[0099] In a specific embodiment provided by the present invention, 0.5-0 mm particles are screened, and the screening results are shown in Table 3 below:

[0100] Table 3: Particle proportions of different particle sizes of mixed powder and pure powder:

[0101]

[0102] Compared with simply manufactured powder, mixed powder has more values ​​at the two ends and fewer values ​​in the middle in particle size distribution. It has a higher content in low particle sizes and has a better filling effect on tiny gaps.

[0103] Example 4

[0104] In a specific implementation manner provided by the present invention, taking water island coke as an example:

[0105] 1. After crushing, the yield ratio of 2-1mm and 1-0.5mm particle sizes of Shuidao coke is 1.5:1; the effective density of 2-1mm and 1-0.5mm particle sizes is measured:

[0106] d 2-1 =2.118g / cm3,

[0107] d 1-0.5 =2.126g / cm3,

[0108] 2. Mix the particles of 2-1mm and 1-0.5mm in a ratio of B:1=1.5:1 and prepare 50g of mixture.

[0109] 3. Perform a tap density test on the 50g particles mixed above and measure their volume.

[0110] V = 49.67 ml;

[0111] 4. Calculate the effective volume V1 of 50 grams of mixed particles:

[0112] V1=[(50×1.5) / (1.5+1)] / d 2-1 +[(50×1) / (1.5+1)] / d 1-0.5

[0113] =(30 / 2.118)+(20 / 2.126)=14.16+9.41=23.57ml;

[0114] 5. Calculate the void volume V2:

[0115] V2=V-V1=49.67-23.57=26.1ml;

[0116] Example 5

[0117] In a specific implementation manner provided by the present invention, taking water island coke as an example:

[0118] 1. The particle size ratio of Mizushima coke 2-1mm and 1-0.5mm was forcibly set to 1.4:1; compared with the actual screening output ratio of 1.5:1.

[0119] 2. Mix 2-1mm and 1-0.5mm particles in a ratio of B:1=1.4:1 and prepare 50g of mixture;

[0120] 3. Perform a tap density test on the 50g particles mixed above and measure their volume.

[0121] V=51.35ml.

[0122] 4. Calculate the effective volume V1 of 50 grams of mixed particles:

[0123] V1=[(50×1.4) / (1.4+1)] / d 2-1 +[(50×1) / (1.4+1)] / d 1-0.5

[0124] =(29.17 / 2.118)+(20.83 / 2.126)=23.68ml;

[0125] 5. Calculate the void volume V2:

[0126] V2=V-V1=51.35-23.68=27.67ml;

[0127] Example 6

[0128] In a specific implementation manner provided by the present invention, taking water island coke as an example:

[0129] 1. The particle size ratio of Mizushima coke 2-1mm and 1-0.5mm was forcibly set to 1.6:1; compared with the actual screening output ratio of 1.5:1.

[0130] 2. Mix 2-1mm and 1-0.5mm particles in a ratio of B:1=1.6:1 and prepare 50g of mixture;

[0131] 3. Perform a tap density test on the 50g particles mixed above and measure their volume.

[0132] V = 51.87 ml;

[0133] 4. Calculate the effective volume V1 of 50 grams of mixed particles:

[0134] V1=[(50×1.6) / (1.6+1)] / d 2-1 +[(50×1) / (1.6+1)] / d 1-0.5

[0135] =(30.77 / 2.118)+(19.23 / 2.126)=23.58ml;

[0136] 5. Calculate the void volume V2:

[0137] V2=V-V1=51.87-23.58=28.29ml;

[0138] The data comparison and conclusion are shown in Table 4 below:

[0139] Table 4: Void volume corresponding to the mixing ratio of 2-1mm and 1-0.5mm particle sizes

[0140]

[0141] From Example 4 to Example 6, it can be concluded that when the mixing ratio is 2-1mm and 1-0.5mm, and the actual output ratio is 1.5:1, the gaps produced by the mixing are the smallest, and the required powder is the least. The demand for product asphalt is the least.

[0142] Example 7

[0143] In a specific embodiment provided by the present invention, the effect of the ratio of small particles and powder on the amount of asphalt and product density is shown in Table 5 below:

[0144] Table 5: Relationship between 0-0.5mm and powder ratio, asphalt quantity and product density

[0145]

[0146] The above technical solution obtains a lower amount of formula oil in the mixed powder, which means that its filling effect is better. In terms of raw product density comparison, the density of the mixed powder product is 0.0116g / cm higher than that of the pure powder product. 3 , but the calcined density is 0.0381g / cm higher 3 This indicates that the asphalt coking value of the product using mixed powder is higher, and it also proves the locking effect of the increase of ultrafine powder on the volatilization of light components of asphalt.

[0147] Example 8

[0148] In a specific embodiment provided by the present invention, the raw material is Mizushima M-grade needle coke, and Φ231mm ultra-high power joint is produced:

[0149] 1. Use Mizushima M-grade needle coke powder, and the powder purity is controlled at 80%.

[0150] 2. Take the raw material and screen it to obtain the undersize material 0.5-0mm under the 0.5mm particle size sieve, and screen it to determine that the percentage of 0.075-0mm in the 0.5-0mm particle size is 15%.

[0151] 3. Calculate the mixing ratio of 0.5-0mm undersize material and 80% purity powder so that the content of 0.075-0mm in the mixed material accounts for 56%;

[0152] X×15%+Y×80%=56%;

[0153] X+Y=100%;

[0154] Calculation: X = 37%; Y = 63%;

[0155] A=X / Y=37% / 63%=0.59;

[0156] The mixing ratio of 0.5-0 mm sieve material and 80% purity powder is: A:1=0.59:1.

[0157] 4. Mix 0.5-0mm and 80% powder in a ratio of 0.59:1 and measure the effective density d of the mixture. 粉料 =2.14g / cm 3 .

[0158] 5. Crush the raw materials to less than 2 mm and measure the yield ratio of 2-1 mm and 1-0.5 mm particle sizes, that is, B:1=1.5:1.

[0159] 6. Determine the effective density of particles with a diameter of 2-1mm and 1-0.5mm:

[0160] d 2-1 =2.118g / cm 3 ,

[0161] d 1-0.5 =2.126g / cm 3 ,

[0162] 7. Mix 2-1mm and 1-0.5mm particles in a ratio of B:1=1.5:1 and prepare 50g of mixture.

[0163] 8. Perform a tap density test on the 50g particles mixed above and measure their volume.

[0164] V=49.67ml.

[0165] 9. Calculate the effective volume V1 of 50 grams of mixed particles:

[0166] V1=[(50×B) / (B+1)] / d 2-1 +[(50×1) / (B+1)] / d 1-0.5

[0167] =[(50×1.5) / (1.5+1)] / d 2-1 +[(50×1) / (1.5+1)] / d 1-0.5

[0168] =(30 / 2.118)+(20 / 2.126)=14.16+9.41=23.57ml; 10. Calculate the void volume V2 in 50g of mixed particles:

[0169] V2=V-V1=49.67-23.57=26.1ml;

[0170] 11. Calculate the mass D of mixed powder that can be filled in V2:

[0171] D=V2×d 粉料 =26.1×2.14=55.854g;

[0172] 12. Calculate the percentage of mixed powder in the sum of 50 grams of mixed particles and mixed powder. 粉料 :

[0173] E 粉料 =[D / (D+50)]×100%

[0174] =[55.854 / (55.854+50)]×100%=52.8%;

[0175] 13. Calculate the percentage of 2-1mm and 1-0.5mm particle sizes:

[0176] C 2-1 =(100%-E 粉料 )×[B / (B+1)]

[0177] =(100%-E 粉料 )×[1.5 / (1.5+1)]=28.32%;

[0178] C 1-0.5 =(100%-E 粉料 )×[1 / (B+1)]

[0179] =(100%-52.8%)×[1 / (1.5+1)]=18.88%; 14. Calculate the usage percentage of 0.5-0 mm sieve material and 80% purity powder:

[0180] C 0.5-0 =E×A / (A+1)

[0181] =52.8%×0.59 / (0.59+1)=19.6%;

[0182] C 粉料 =E×1 / (A+1)

[0183] =52.8%×1 / (0.59+1)=33.2%;

[0184] 15. The formula is as follows: 2-1mm accounts for 28.32%;

[0185] 1-0.5mm: 18.88%;

[0186] 0.5-0mm undersize: 19.6%;

[0187] The proportion of 80% purity powder: 33.2%;

[0188] 16. Wet mixing time = [(C 2-1 +C 1-0.5 -27%)×2.5 / 10%]+40

[0189] =[(28.32%+18.88%-27%)×2.5 / 10%]+40=45.05min;

[0190] That is, the wet mixing time is 45.05min

[0191] Example 9

[0192] The raw material is high-power roasted crushed steel, and Φ231mm high-power joints are produced.

[0193] 1. Grinding, the purity of grinding is controlled to 80%,

[0194] 2. Take the raw material and screen it to obtain the undersize material 0.5-0mm under the 0.5mm particle size sieve, and screen it to determine that the percentage of 0.075-0mm in the 0.5-0mm particle size is 18%.

[0195] 3. Calculate the mixing ratio of 0.5-0mm undersize material and 80% purity powder so that the 0.075-0mm content in the mixed material accounts for 54%.

[0196] X×18%+Y×80%=54%;

[0197] X+Y=100%

[0198] X = 41.9%; Y = 58.1%

[0199] A=X / Y=41.9% / 58.1%=0.72

[0200] The mixing ratio of 0.5-0mm sieve material and 80% purity powder is: A:1=0.72:1.

[0201] 4. Mix 0.5-0mm and 80% powder in a ratio of 0.72:1 and measure the effective density d of the mixture. 粉料 =2.049g / cm 3

[0202] 5. Crush the raw materials to less than 2mm, and measure the yield ratio of 2-1mm and 1-0.5mm particle sizes, that is, B:1=1.3:1.

[0203] 6. Determine the effective density of particles with a diameter of 2-1mm and 1-0.5mm:

[0204] d 2-1 =1.997g / cm 3

[0205] d 1-0.5 =2.006g / cm 3

[0206] 7. Mix the particles of 2-1mm and 1-0.5mm in a ratio of B:1=1.3:1 and prepare 50g of mixture.

[0207] 8. Perform a tap density test on the 50g particles mixed above, and measure its volume to be V=52.3ml.

[0208] 9. Calculate the effective volume V1 of 50 grams of mixed particles:

[0209] V1=[(50×B) / (B+1)] / d 2-1 +[(50×1) / (B+1)] / d 1-0.5

[0210] =[(50×1.3) / (1.3+1)] / d 2-1 +[(50×1) / (1.3+1)] / d 1-0.5 =24.99ml;

[0211] 10. Calculate the void volume V2 in 50 grams of mixed particles:

[0212] V2=V-V1=52.3-24.99=27.31ml;

[0213] 11. Calculate the mass D of mixed powder that can be filled in V2:

[0214] D=V2×d 粉料 =27.31×2.049=55.96g;

[0215] 12. Calculate the percentage of mixed powder in the sum of 50 grams of mixed particles and mixed powder E powder:

[0216] E 粉料 =[D / (D+50)]×100%

[0217] =[55.96 / (55.96+50)]×100%=52.8%;

[0218] 13. Calculate the percentage of 2-1mm and 1-0.5mm particle sizes:

[0219] C 2-1 =(100%-E 粉料 )×[B / (B+1)]

[0220] =(100%-52.8%)×(1.3 / (1.3+1))=26.68%;

[0221] C 1-0.5 =(100%-E 粉料 )×[1 / (B+1)]

[0222] =(100%-52.8%)×(1 / (1.3+1))=20.52%;

[0223] 14. Calculate the usage percentage of 0.5-0mm undersize material and 80% purity powder:

[0224] C 0.5-0 =E×A / (A+1)

[0225] =52.8%×0.72 / (0.72+1)=22.1%;

[0226] C 粉料 =E×1 / (A+1)

[0227] =52.8%×1 / (0.72+1)=30.7%;

[0228] 15. The formula is as follows:

[0229] 2-1mm: 26.68%;

[0230] 1-0.5mm: 20.52%;

[0231] 0.5-0mm undersize material proportion: 22.1%;

[0232] The proportion of 80% purity powder: 30.7%;

[0233] 16. Wet mixing time = [(C 2-1 +C 1-0.5 -27%)×2.5 / 10%]+40

[0234] =[(26.68%+20.52%-27%)×2.5 / 10%]+40=45.05min;

[0235] That is, the wet mixing time is 45.05 minutes.

[0236] Example 10

[0237] The raw material is Daqing petroleum coke, and Φ231mm ordinary power joints are produced.

[0238] 1. Use Daqing petroleum coke to grind powder, and the purity of the powder is controlled at 80%.

[0239] 2. Take the raw material and screen it to obtain the undersize material 0.5-0mm under the 0.5mm particle size sieve, and screen it to determine the percentage of 0.075-0mm in the 0.5-0mm particle size, which is 13%.

[0240] 3. Calculate the mixing ratio of 0.5-0mm undersize material and 80% purity powder so that the 0.075-0mm content in the mixed material accounts for 55%.

[0241] X×13%+Y×80%=55%;

[0242] X+Y=100%

[0243] Calculation: X = 37.3%; Y = 62.7%;

[0244] A=X / Y=37.3% / 62.7%=0.595

[0245] The mixing ratio of 0.5-0 mm sieve material and 80% purity powder is: A:1=0.595:1.

[0246] 4. Mix 0.5-0mm and 80% powder in a ratio of 0.595:1 and measure the effective density d of the mixture. 粉料 =2.127g / cm 3 .

[0247] 5. Crush the raw materials to less than 2 mm and measure the output ratio of 2-1 mm and 1-0.5 mm particle sizes, that is, B:1=1.4:1.

[0248] 6. Determine the effective density of particles with a diameter of 2-1mm and 1-0.5mm:

[0249] d 2-1 =2.029g / cm 3 ,

[0250] d 1-0.5 =2.059g / cm 3 ,

[0251] 7. Mix the particles of 2-1mm and 1-0.5mm in a ratio of B:1=1.4:1 and prepare 50g of mixture.

[0252] 8. Perform a tap density test on the 50g particles mixed above and measure their volume.

[0253] V=68ml.

[0254] 9. Calculate the effective volume V1 of 50 grams of mixed particles:

[0255] V1=[(50×B) / (B+1)] / d 2-1 +[(50×1) / (B+1)] / d 1-0.5

[0256] =[(50×1.4) / (1.4+1)] / d 2-1 +[(50×1) / (1.4+1)] / d 1-0.5

[0257] =24.49ml;

[0258] 10. Calculate the void volume V2 in 50 grams of mixed particles:

[0259] V2=V-V1=68-24.49=43.51ml;

[0260] 11. Calculate the mass D of mixed powder that can be filled in V2:

[0261] D=V2×d 粉料 =43.51×2.127=92.546g;

[0262] 12. Calculate the percentage of mixed powder in the sum of 50 grams of mixed particles and mixed powder E powder:

[0263] E 粉料 =[D / (D+50)]×100%

[0264] =[92.546 / (92.546+50)]×100%=64.9%;

[0265] 13. Calculate the percentage of 2-1mm and 1-0.5mm particle sizes:

[0266] C 2-1 =(100%-E 粉料 )×[B / (B+1)]

[0267] =(100%-64.9%)×[1.4 / (1.4+1)]=20.475%;

[0268] C 1-0.5 =(100%-E 粉料 )×[1 / (B+1)]

[0269] =(100%-64.9%)×(1 / 2.4)=14.625%;

[0270] 14. Calculate the usage percentage of 0.5-0mm undersize material and 80% purity powder:

[0271] C 0.5-0 =E×A / (A+1)

[0272] =64.9%×0.595 / (0.595+1)=24.21%;

[0273] C 粉料 =E×1 / (A+1)

[0274] =64.9%×1 / (0.595+1)=40.69%;

[0275] 15. The formula is as follows:

[0276] 2-1mm: 20.475%;

[0277] 1-0.5mm: 14.625%;

[0278] 0.5-0mm undersize material proportion: 24.21%;

[0279] The proportion of 80% purity powder: 40.69%;

[0280] 16. Wet mixing time = [(C 2-1 +C 1-0.5 -27%)×2.5 / 10%]+40

[0281] =[(20.475+14.625-27%)×2.5 / 10%]+40=42.025min;

[0282] That is, the wet mixing time is 42.025 minutes.

[0283] Embodiment 11

[0284] The raw product volume density and the baked product volume density of the product of the present invention are significantly increased, the asphalt dosage is significantly reduced, and the various physical and chemical indicators of the product are significantly improved. The specific indicators are shown in Table 6 below.

[0285] Table 6: Density changes of raw products and calcined densities of Φ333mm ultra-high power graphite electrode joints with original and optimized formulas

[0286]

[0287] In summary, the present invention proposes a method for optimizing the design of dry material formula for graphite electrode joints, adopts large blocks of material per unit volume, crushes the large blocks of material, and directly adopts the output ratio of large particles with a particle size of 2-1mm and 1-0.5mm after screening the crushed large blocks per unit volume as the ratio. There is no need to calculate the usage of large particle raw materials in advance, which reduces the problem of large deviations between actual production results and theoretical results caused by the superposition of human errors, makes the formula combination more reasonable, leads to an increase in product volume density, reduces the use of asphalt, improves product quality, and reduces enterprise production costs.

Claims

1. A method for optimizing the dry material formula of a graphite electrode joint, characterized in that: The following steps are involved: (1) Limiting the particle size of 2-1mm and 1-0.5mm: Take a unit volume of large blocks and crush them to a particle size of less than 2mm, and screen the resulting crushed materials according to different particle sizes; (2) The yield ratio of particles with a particle size of 2-1 mm and 1-0.5 mm in the sieved crushed material is determined as B:1: The effective density of particles with a particle size of 2-1 mm is determined as d 2-1 , the effective density of the particle size of 1-0.5 mm is determined as d 1-0.5 ; (3) Determine the mixing ratio of the 0.5-0 mm particle size undersize material and the powder of fixed purity; (4) Conducting a tap density test on 50 g of mixed large particles, and calculating the proportions of particles with a particle size of 2-1 mm, particles with a particle size of 1-0.5 mm, particles with a particle size of 0.5-0 mm, and powders with a fixed purity in the technical formula; (5) Calculate the wet mixing time in the kneading time.

2. The method for optimizing the dry material formula of a graphite electrode joint according to claim 1, characterized in that: The step (2) is specifically as follows: The effective volume and mass of the 2-1mm and 1-0.5mm sized particles after screening were measured, and the d was determined by the ratio of the mass to the effective volume. 2-1 and d 1-0.5 .

3. The method for optimizing the dry material formula of a graphite electrode joint according to claim 1, characterized in that: The step (3) is specifically as follows: The 0.5-0mm small particles after screening are further screened, and the content of 0.075-0mm in the 0.5-0mm particle size is K%. The 0.5-0mm particle size and the powder of fixed purity are mixed. When the proportion of 0.5-0mm in the mixture is X, the proportion of powder in the mixture is Y, and the purity of the powder of fixed purity is N%, the effective density of the mixture is measured as d 粉料 , the proportion of 0.075-0mm in the mixed material is: After the needle coke material is mixed, the content of 0.075-0 mm accounts for 56%; After the roasted and crushed materials are mixed, the content of 0.075-0 mm accounts for 54% of the materials; After petroleum coke materials are mixed, the content of 0.075-0mm accounts for 55%; Taking needle coke as an example, the calculation is as follows: X+Y=100% Formula 1 X×K%+Y×N%,=56%; Formula 2 The mixing ratio of small particles with a particle size of 0.5-0 mm after screening and powder with a fixed purity is X:Y=A:

1.

4. The method for optimizing the dry material formula of a graphite electrode joint according to claim 3, characterized in that: The 0.075-0 mm particle size is further divided into 0.015-0 mm, 0.038-0.015 mm and 0.075-0.038 mm, and the filling amount of each particle size is controlled so that the particle sizes within 0.075-0 mm are filled with each other.

5. The method for optimizing the dry material formula of a graphite electrode joint according to claim 3, characterized in that: The purity of the powder with fixed purity is 80%.

6. The method for optimizing the dry material formula of a graphite electrode joint according to claim 1, characterized in that: The step (4) is specifically as follows: Take 50 grams of mixed large particles of 2-1mm and 1-0.5mm with a mixing ratio of B:1 for tap density test, and measure its volume as V. Calculate the effective volume V1 of 50g mixed particles, which is calculated as follows: V1 = [(50×B) / (B + 1)] / d 2-1 + [(50×1) / (B + 1)] / d 1-0.5 Equation 3 The void volume in 50g of mixed particles is V2, V2 = V-V1 The mass D of the mixed powder that can be filled in V2 is calculated as follows: D=V2×d 粉料 Formula 4 The percentage of mixed powder to the sum of 50 grams of mixed particles and mixed powder is E 粉料 , calculated as follows: E 粉料 =[D / (D+50)]×100% Formula 5 The percentage of 2-1mm particle size particles in the technical formula is C 2-1 , the percentage of 1-0.5mm particle size in the technical formula is C 1-0.5 , calculated as follows: C 2-1 =(100%-E 粉料 )×[B / (B+1)] Formula 6 C 1-0.5 =(100%-E 粉料 )×[1 / (B+1)] Formula 7 The percentages of 0.5-0 mm particle size particles and powders of fixed purity in the technical formula are C 0.5-0 , C 粉料 , calculated as follows: C 0.5-0 =E×A / (A+1) Formula 8 C 粉料 =E×1 / (A+1) Formula 9.

7. The method for optimizing the dry material formula of a graphite electrode joint according to claim 1, characterized in that: The step (5) is specifically as follows: The wet mixing time in the kneading time is calculated as follows: [(C 2-1 +C 1-0.5 -27%)×2.5 / 10%]+40 formula 10.

8. The method for optimizing the dry material formula of a graphite electrode joint according to claim 7, characterized in that: The 27% of the wet mixing time is the sum of the percentages of 2-1 mm and 1-0.5 mm in the initial technical formula, and the 40 of the wet mixing time is 40 minutes of wet mixing time in the original technical formula.

Citation Information

Patent Citations

  • Graphite electrode connector and preparation method thereof

    CN106631084A

  • Design method of dry material size fraction composition in graphite electrode joint formula

    CN113860874A

  • Improvements in or relating to the production of graphite

    GB883021A

  • Preparation method for high-strength graphite electrode

    WO2024082709A1